2021
DOI: 10.47340/mjhss.v2i2.1.2021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Associated Risk Factors Among Women in a Rural Community in Bangladesh: A Cross-Sectional Study

Abstract: The purpose of this cross-sectional quantitative study was to identify the prevalence and associated risk factors of hypertension among rural women. Data collection was carried out between March to June 2019 among 380 women in Kumarkhali Upazila, Kushtia, Bangladesh. Participants were interviewed with a structured questionnaire including background characteristics, anthropometric measurements, prevalence, and risk factors of hypertension. IBM SPSS version 25 was used for analyzing the data. The prevalence of h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Another study discovered that the overall prevalence of hypertension was around 26 %; while 20 % was among men, and 32 % was among women [ 16 ]. In a recent study, overall hypertension and prehypertension among rural women were found as around 21 % and 17 %, respectively [ 17 ]. Furthermore, in comparison to men, rural women are usually faced with less availability and accessibility to information and related sources and less exposure to media and intensive campaigns, impacting their health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Another study discovered that the overall prevalence of hypertension was around 26 %; while 20 % was among men, and 32 % was among women [ 16 ]. In a recent study, overall hypertension and prehypertension among rural women were found as around 21 % and 17 %, respectively [ 17 ]. Furthermore, in comparison to men, rural women are usually faced with less availability and accessibility to information and related sources and less exposure to media and intensive campaigns, impacting their health outcomes.…”
Section: Introductionmentioning
confidence: 99%